Indigenous cattle of Manipur - Characterization and performance evaluation - PUNDIR, R K; SINGH, P K; DANGI, P S; KUMAR, A; SINGH, N B; SINGH, P K; SADANA, D K (The Indian Journal of Animal Sciences, 2015)
Manipur had 2.63 lakh cattle head including 2.19 lakh indigenous and 0.44 lakh crossbred in the year 2012. The trends in cattle population during the years 2003-07 showed a decline of 18.32% in total cattle population, 20.86% in indigenous cattle and 6.06% in crossbred cattle. There is not a single registered breed of cattle from the state. In the present study an attempt was made to characterize and evaluate indigenous cattle of the state as there is no information available in the literature on these cattle. Surveys were conducted in Imphal East, Imphal West (Valley districts) and Churachandpur (Hilly district) districts. Farmers (83) and animals (363) of different age and sex from 13 villages were included in the present study. The indigenous cattle of Manipur are of medium size, stout and hardy. Animals were reared mainly on extensive system of management i.e. grazing from morning to evening. During December to June when rice crop is there, animals were provided rice bran and rice waste as concentrate. The body colour was different i.e. brown (76%), black (12%), gray (4%) and spotted with black or white patches on brown body (8%). Bullocks had medium hump. Horns were small, black (82%) or gray (18%) in colour. Udder was small, not well developed and milk veins were not prominent. Temperament was docile in all the cases. The average body length, height at wither, heart girth, paunch girth, ear length, face length, tail length without switch and horn length in cows were measured. Cows and bullocks did not differ significantly in all the morphometric traits. The average daily milk yield was 2.65±0.18 kg (2.0 to 4.5 kg). Animals showed uniformity in physical and morphometric traits. Cows showed good potential for milk production and there is a need of systematic genetic improvement programs to develop and improve the milk productivity.